The Effect of Quartz Sand on Structural and Optical Properties of Dy3+ Doped P2O5-CaO-BaO-Gd2O3 Glasses - Panggabean, Jonny H.; Br Sembiring, Novita Madalena; Simanullang, Elyzabeth; Rajagukguk, Juniastel; Sarumaha, C.S.; Kaewkhao, J. (The Physical Society of Indonesia, 2025)
This study investigates the influence of quartz sand incorporation on the structural and optical properties of Dy³⁺ doped P₂O₅–CaO–BaO–Gd₂O₃ phosphate glasses. The glass samples were synthesized using the conventional melt-quenching technique, with varying concentrations of quartz sand as a partial substitution of P₂O₅. Structural characterization was carried out using X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy, which confirmed the formation of an amorphous glass network and the presence of phosphate, silicate, and modifier-related vibrational bands. The optical absorption spectra, recorded via UV–Vis spectroscopy, revealed characteristic f–f transitions of Dy³⁺ ions, indicating their successful incorporation into the glass matrix. The intensity ratio of yellow to blue emission was found to be influenced by the quartz sand content, suggesting a significant role of SiO₂ in modifying the local environment around Dy³⁺ ions. These results highlight the potential of quartz-sand-modified phosphate glasses as promising candidates for photonic and luminescent device applications.